Value of data - Slánský, David (2021)
Data and information are without doubts one the most important assets of the 21st century. However, the mankind is still not able to consistently and reliably measure their impact(s). Therefore, a program has been set up by KPMG, Data & Business expert platform and Department of Information Technologies, Prague University of Economics and Business with support of UC Berkeley Sutardja Center for Entrepreneurship & Technology) to create and environment for overall data value measurement - KPMG Infonomics Engine. While certain modules of the Engine deal with identification and description of business stories through which data delivers the value to organizations (Quantified Opportunities Repository) and with identification, description and quality management of data elements in an organization (Intelligent Data Discovery Platform), this thesis sets out the heart of the environment – the Overall Data Value Calculation Methodology – an approach to putting together fractional assessment of additional value data brings to an organization and calculating the overall value of data in the defined multidimensional space. The document defines not only the single data value calculation elements interactions, their behaviour and possible impacts, but also quantifies these impacts and puts everything in powerful data storage for the overall value calculation together with user-friendly presentation layer for simple browsing through the associated information. The newly defined methodology and reporting environment are then applied on a pilot case to prove its usability and stability and to backwards update the methodology. Not only this – the further steps, especially in the area of Artificial Intelligence support and further overall solution functionality – are defined for the above-mentioned program team.